Analisis Ketidaksesuaian Stok Barang Jadi Antara Inventory dan Barang Aktual di PT. Sumi Asih Menggunakan Metode DMAIC - Berniliyus, Akwila; Windyatri, Hasyrani; Intani, Arvita Emarilis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Inventory management plays a crucial role in ensuring smooth production processes and fulfilling customer orders in manufacturing companies. However, discrepancies between physical stock and system records frequently occur, leading to inefficiencies and increased operational costs. This research was conducted at PT. Sumi Asih to identify the primary causes of stock discrepancies and provide improvement recommendations using the DMAIC (Define, Measure, Analyze, Improve, Control) method. The study analyzed stock records from August 2023 to January 2024 using tools such as Pareto diagrams, Fishbone diagrams, and the 5S method. The findings revealed that 82% of stock discrepancies were due to ongoing in/out transactions, 12% resulted from defective goods undergoing remelting, and 6% were due to unrecorded items. The proposed improvements include implementing the 5S method to enhance warehouse organization and stricter monitoring of stock recording. These measures are expected to reduce stock discrepancies by up to 50% and improve warehouse operational efficiency.